Corpo e política: cartografias da população em situação de rua - Souza, Josiane Cristina Orlando de (2017)
We see in the contemporary times the emergence of specific public policies for the homless population, with strategies and specialized services for care. In the face of Foucault's observation that policies increasingly include biopolitical devices that aim to control the life of the population, the objective of this work was to analyze the possible connections between body and politics, and more specifically, the body of the street population and The public policies aimed at him. Not surprisingly, people living on the streets, from ancient times, are excluded from social life, either because of their extreme poverty or because of the society's fear that they could risk and insecure the good functioning of the city. Given the times, but not the strategies, it is still possible to verify such exclusion even in the face of specific laws and interventions that should offer protection and social reintegration. In this study, we identified how the National Policy for the Population in Street Situation (PNPSR) and the National Social Assistance Policy (PNAS) still operate under hygienic bias, producing dependent and dependent subjectivities. However, there are ways to resist the biopolitical onslaughts, and leave a captured body for the production of a potent body that is able to reinvent new ways of life.